Tahsin Maharat AlKalam Bi Altariqat Al Mubasyarah - Fuji, Fuji Astuti; Alfisyahrina, Khuzaimah; Nisak, Rahmatun (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to determine the steps of teaching Arabic speaking skills with direct methods and the efforts of the Arabic Language Education Study Program and lecturers in improving speaking skills with direct methods in the Arabic Language Education Study Program at the Langsa State Islamic Institute. The method used in this research is a case study method with a descriptive analysis approach, and to collect data, researchers use observation and interviews as research instruments. In analyzing the data, researchers chose to collect data, reduce data, present data, then draw conclusions. The data sources in this study are the head of the Arabic language education study program, lecturers teaching speaking skills courses and fifth semester students in the Arabic language education study program at the Langsa State Islamic Institute. The results showed that the Arabic Language Education Program, Langsa State Islamic Institute, has applied the direct method as the most important method in teaching speaking skills, and this learning takes place in three stages, namely the planning stage, the implementation stage, and finally the evaluation stage. In order to optimize the teaching of speaking skills with direct methods, the Arabic Language Education study program and lecturers make several efforts, the most important of which are: The Department of Arabic Language Education requires lecturers to speak Arabic in class, lecturers use more Arabic references in teaching, hold an Arabic language environment especially in class and office, and students will not be served except by speaking Arabic. thus the learning of speaking skills using direct methods can be optimized well.